Business ethics : ethical decision making and cases - Ferrell, O. C.
"Business Ethics fulfills the need for a practical, applied text at the core of the ethics course or used as a supplement in other undergraduate and graduate courses. This accessible, up-to-date text covers the complex environment in which managers confront ethical decision making. Through this managerial framework, the authors cover the overall concepts, processes, and best practices associated with successful business ethics programs--helping students to see how ethics can be integrated into key strategic business decisions. Pedagogical tools help students to prepare for real-world ethical dilemmas instead of focusing on intellectual reasoning or a philosophical discussion of ideas.A total of 18 cases reinforce the text's applied approach to ethics and cover a range of organizations and topics, such as "Martha Stewart's Insider Trading Scandal," "Enron: The Case of the Tilted 'E, '" "Tyco International, Ltd.," and "WorldCom."Chapter 10, "Business Ethics in a Global Economy," includes information on best practices, ethics audits, and disaster recovery planning to increase students' awareness of cross-national ethical issues and develop their strategic skills for planning and working through disasters." - product description.